(3BdjGJ GdYhdeI GdGbJUGOjI h BKGQgG GdeSJbHdjI aj GdGbJUGO GdYQHjs - (3gjaGA YHO GdQMef jGSjf(B, (3GdJcQjJjs ((3YeGf(B:s (3OGQ GdMGeO(B,s, 2009)
(3eaghe GdYhdeI , GdeQLYjI GdacQjI h GdJGQjNjI ddYhdeI , GdGReGJ GdGbJUGOjI h GdeGdjI ddQCSeGdjI , GdJWhQGdYdej h GdJbfj aj GdYGde , OhGaY GdfXGe GdQCSeGdj ddJSQjY aj HdhZ GdeQMdI GdGNjQI ddYhdeI (B: (3OhGaY GdgjeI h GdGSJMhGP , OGaY GdNdGU ef GdJVNe GdQchOj , OGaY QOY GdJWhQGdGbJUGOj h GdKbGaj h GdGYdGej dOhd GdLfhH , JeQjQ GdeTQhYGJ GdQCSeGdjI h GdUgjhfjI ,GdYhdI h BdjGJ GdGSJKeGQ (B: (3JMhjd GdbWGY GdYGe Gdi GdbWGY GdNGU , JfTTjW GdTQcGJ YGHQI GdbhejGJ , GdYhdeI h BdjI JMQjQ GdJLGQI GdOhdjI (B: (3JMQjQ GdJLGQI GdOhdjI hGMcGe GdSjWQh Ydi GdedcjI GdacQjI , GYGOI JQJjH GdYGde Ydi CSGS GdJcJdGJ GdGbJUGOjI , CKQ GdYhdeIYdi eSJbHd GdGbJUGO GdYQHj (B.s
(3eQGLY U(B.635 (3,edGMb U(B.621s
Keywords: (3GdEbJUGO GdYGdejs; (3GdGbJUGO GdYQHjs; (3GdGbJUGO(B- (3GdHdOGf GdYQHjIs; (3GdYhdeIs; (3GdYhdeI GdGbJUGOjIs